IMPLEMENTASI WEBSITE SEDERHANA MENGGUNAKAN HTML DAN CSS SEBAGAI MEDIA INFORMASI DIGITAL SISWA MTS PONDOK PESANTREN IBNU UMAR TAHFIDZ BOARDING SCHOOL - Nurhasanah; Laveryl Zavi Pratama; Noval Ilyas Immaduddin; Salim Nur Rohman; Raditya Prima; Marten Ricno Imuly; Muhamad Arul Ardiansyah; Adi Riskiyanto; Muhamad Rafif Fadilah Ratama; Rayhan Rizki Wijaya (Abdi Jurnal Publikasi, 2026)
Basic website development learning is an essential skill in the digital era, particularly for junior secondary school students. This Community Service Program (PKM) aims to implement simple website development learning using HTML and CSS as a digital information medium for students of MTS Pondok Pesantren Ibnu Umar Tahfidz Boarding School. The program was conducted through basic material delivery, website design introduction, and hands-on practice. An educative-participatory approach was applied by actively involving students in the learning process. Data were collected through observation and documentation. The results indicate improvements in students’ understanding of basic website concepts, technical skills, and learning motivation toward digital technology. This program demonstrates that practice-based simple website development learning is effective in supporting students’ digital literacy and can serve as a technology-based learning model in schools.